Uma análise das metodologias de ensino de química publicadas em periódicos - (:unkn) unknown (Universidade Federal do Pampa, 2017)
This work describes a bibliographical research, qualitative and exploratory, in which the purpose was to investigate articles published in journals indexed in the Teaching of Chemistry to identify which teaching methodologies are being developed. The research problems that guided this work were: What are the teaching methodologies most used in published articles in the area of Teaching Chemistry? Among the most used methodologies, what are the theoretical references that support this teaching method? In view of the problems presented above and in search of answers, six journals from the area of Chemistry and / or Science Teaching were elected in a period of ten years from 2007 to 2016. From this search, 23 articles were found. The use of the terms "Teaching Methodology", "Teaching Method" and / or "Teaching Strategy", in their titles, abstract and / or keywords, were used as selection criteria. For the analysis, we sought to know better these publications, from the place, the researchers, the year, for whom (level of education) as well as the thematic that these works were developed. We note that most publications have a variety of methodologies, which focus on the southeastern region of the country. As considerations, we have that the work brought to the teacher in formation a relevant contribution, at the moment that it is observed how can be developed the scientific concepts in the classroom.
Keywords: Ensino de química; Metodologias; Estratégias de ensino; Chemistry teaching; Methodologies; Teaching strategies; Educação; Education; Ciências da natureza; Natural Sciences; CNPQ::CIENCIAS EXATAS E DA TERRA